Grid code compliant controllers for Multi-terminal HVDC grids aimed to integrate wind power: assessing their impact on the operational security of a real-world system. (December 2017) - Irazabal, I. Azpiri; Ciapessoni, E.; Cirio, D.; Glasdam, J.; Lund, P.; Pitto, A.
Abstract: Exploiting multi-terminal High Voltage Direct Current (MTDC) grids for offshore wind park integration into continental bulk AC system raises several technical challenges, in particular the verification of the compliance of MTDC grids and offshore wind parks to the performance requirements (in terms of frequency, voltage support and fault ride through) which are being established by the grid codes, and the availability of general and customizable models to simulate their response. This work is aimed to provide a set of "open access" general models, able to fulfil the grid code requirements if suitably tuned, enabling the TSOs to perform their analyses without relying exclusively on vendor-specific models. In order to verify the realistic response of these models, an example of MTDC grid is simulated, connecting it to plausible operating scenarios of a real world AC system (the West Denmark grid) in target year 2020: some indications to properly tune control parameters are provided together with the results of several simulations aimed to check the fulfilment of grid code requirements in case of typical contingencies.